(untitled) (Global Journal of Management and Business Research, 2024)
From bullshit jobs to bullshit people the relevance of the individual within the group has consistently been a determining factor in their social value and personal esteem The advent of new technologies particularly artificial intelligence AI poses an existential question to humanity about its place in a world rapidly saturated by AI The latter has propelled the evolution of professions at an unparalleled speed a challenge the academic world struggles to manage If the new era of the university has indeed arrived it must then redefine its role as an intellectual institution to avoid a general mediocrity of profiles a pitfall it had encountered in its trajectory as an entrepreneurial university It is imperative for the university to ensure the democratization of human intelligence a crucial element in the strategic management of the advent of artificial intelligence and guarantee social equity in access to knowledge Thus it is appropriate to assign to E-learning the function of certifying and preparing the technical profiles necessary for the practical functioning of society